Training and Human Resources Development Project : Measure 1 : Language training program - Dialogue McGill (2005)
The language training program presented is part of the Training and Human Resources Development Project that McGill University is to implement. This project is designed to ensure that English-speaking Quebecers obtain equitable access, in their language, to the range of health and social services offered to the entire population. The project has been elaborated against a backdrop of sociodemographic changes affecting Québec’s English-speaking communities, the adoption of new legislation modifying the organization of work, and the modernization of the health and social services system. It will be geared to clinical projects now being prepared pertaining to the organization of services. The project is an additional means of reviewing and implementing regional programs of access to health and social services in the English language, as stipulated by the Act respecting health services and social services.

Caring for elderly parents? Balancing family with work or studies? You may be part of the sandwich generation... - Howarth, Kelly (2005)